Development of a Project-Based Learning Assessment System to Improve Students’ Competence - Wening Patmi Rahayu; Hidayatin Hidayatin; Madziatul Churiyah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
The study aims to develop a project-based learning assessment system to improve students’ competence. Data were obtained using the Research and Development (R&D) methods adopted from Borg & Gall which comprised of 8 stages. The research products were tested by using the construct and content validations conducted by 2 lecturers and 1 teacher, respectively. Furthermore, students’ competence was analyzed by measuring their cognitive, affective and psychomotor domains. The product developed obtained highly valid criteria in the affective, cognitive, and psychomotor domains with scores of 84.6%, 84.2% and 84%, respectively. In addition, the results of content validation obtained highly valid criteria in the affective, cognitive, and psychomotor domains with scores of 90%, 93.3%, and 92%. Furthermore, the results of field testing obtained a score of 82% by 1 archival teacher and 82.77% by 30 students which showed that the assessment instrument received a good response and feasible for use in learning. The improvement in competence was measured by projects made in the instrument, and it led to a significant improvement in competence before using the assessment as learning instrument.